Pengaruh Kepemimpinan, Lingkungan Kerja, dan Kompensasi dalam Perspektif Islam terhadap Kinerja Karyawan RS PKU Muhammadiyah Gamping Sleman Yogyakarta - Ali Rochmad; Wijiharta Wijiharta (At-Tauzi : Jurnal Ekonomi Islam, 2016)
This study aims to determine the effect of leadership, work environment, and compensation in the Islamic perspective on performance. The sample consisted of 76 employees of PKU Muhammadiyah Gamping Hospital, Sleman Yogyakarta. Data analysis using SPSS 17. The correlation test results show that leadership (X1) has a moderately positive correlation (r= 0.455), work environment (X2) has a strong positive correlation (r= 0.709), compensation (X3) has a strong positive correlation (r= 0.654). . on employee performance (Y). All correlation coefficient values ​​are significant. The strongest correlation is between the work environment (X2) and employee performance (Y). The results of the regression test resulted in a regression notation Y= 5.232 + 0.081 X1 + 0.536 X2 + 0.145 X3. All regression coefficient values ​​are significant. The work environment (X2) has the strongest effect on employee performance (Y) with a regression coefficient value of 0.536, which means that each work environment increases by one unit will increase employee performance by 1.536 units. This research model has a determination value (R square) of 0.511, which means that leadership, work environment, and compensation contribute to employee performance by 51.1%, while the other 48.9% is influenced by other factors.